A Study of Language Use Impact in Radio Broadcasting: A Linguistic and Big Data Integration Approach. (24th September 2022) - Praise Chukwunalu, Young; Nwankwere, Angela U. N.; Orji, Dereck A.; Shah, MohdAsif
Abstract : Broadcasting more culturally educating and language-reviving contents are ways radio stations can help revitalize indigenous languages in Delta North in Nigeria. The challenges faced in communicating through indigenous dialects on radio stations are majorly caused by the lack of indigenous language professionals and linguists in the broadcast stations. The absence of these professionals is a major constraint to the development of the community. The broadcast media can help manage multilingualism through the introduction of new words which would give little or no room for lexicon dearth but would expand the language lexicon. Using these dialects during broadcast gives relevance to all dialects, reduces language dearth, and keeps people connected to their culture. Programmes anchored in indigenous dialects enhance the vocabulary, comprehension, and language vitality of the language. The study examined the impact of local language used in radio broadcasting using a descriptive big data survey research design. The study's population comprises of all the inhabitants of Delta North from which a sample of 10 broadcast staff and 120 radio listeners in Delta North Senatorial District in Nigeria was drawn using a stratified random sampling technique. The instrument of data collection was a structured questionnaire with closed questions and a self-structured interview. The sample employed frequency distribution tables, percentages, and charts in the presentation and analysis of data. The results revealed that majority of the respondents in Delta North listened to radio broadcast indicating that the use of indigenous dialects/language can have massive impact on the people. The study also found that majority of the respondents use indigenous languages in their day-to-day activities, with English being used majorly only in schools. The study recommends, among others, that the National Broadcasting Commission review their policy on the allocated time of broadcast in indigenous languages and that more indigenous language experts and linguists should be incorporated into the broadcast system.